Perlindungan Hukum Pencipta Lagu Aisyah Asal Malaysia Atas Tindakan Strike Konten Youtube Oleh Musisi Indonesia - Nonny Relinda Elok Paraswari (Journal of Private and Economic Law, 2022)
ABSTRACT: in its development, the existence of cases in the field of copyright does not only involve creators in one country only, but also involves creators from other countries, such as the case that recently occurred, namely the case between songwriter Aisyah a Malaysian named Angah Razif with an Indonesian musician named Harlin Pasili Ansori. This case began when an Indonesian musician named Harlin Pasili Ansori claimed that Aisyah’s song was composed by Angah Razif which was sung by Projector Band plagiarized the melody of his song entitled Half Trip to Bait Al Hamid. Harlin submitted a strike report for the content of Aisyah’s song to the youtube side, as a result of the report, the youtube took a strike to the content of the song Aisyah created by Angah Razif presented by Projector Band, so the content of Aisyah’s song is lost from the official channel Projector Band. From the claims made by Harlin giving the impact of loss to Angah as the creator of Aisyah’s song that is materially and immaterially. In international treaties, to be exact, Berne Convention has guaranteed the rights owned by an creator. Protection of a creation is provided by the Berne Convention and also the laws of each participating country. In other words, every country participants are obliged to provide protection to the creation of all citizens countries from all participating countries that are participants in the Berne Convention. Where the protection of the creation will be further regulated by: the law of the country of origin of the creator or the law of the country of place claimed protection. In this article, we will explain more about protection the law against the songwriter Aisyah from Malaysia with reference to Indonesian state laws and regulations, because in this case the perpetrators of copyright infringement are indonesian citizens. The type of research that used is by using normative juridical. Keywords: Legal Protection, Creator, Youtube Content Strike ABSTRACT: in its development, the existence of cases in the field of copyright does not only involve creators in one country only, but also involves creators from other countries, such as the case that recently occurred, namely the case between songwriter Aisyah a Malaysian named Angah Razif with an Indonesian musician named Harlin Pasili Ansori. This case began when an Indonesian musician named Harlin Pasili Ansori claimed that Aisyah’s song was composed by Angah Razif which was sung by Projector Band plagiarized the melody of his song entitled Half Trip to Bait Al Hamid. Harlin submitted a strike report for the content of Aisyah’s song to the youtube side, as a result of the report, the youtube took a strike to the content of the song Aisyah created by Angah Razif presented by Projector Band, so the content of Aisyah’s song is lost from the official channel Projector Band. From the claims made by Harlin giving the impact of loss to Angah as the creator of Aisyah’s song that is materially and immaterially. In international treaties, to be exact, Berne Convention has guaranteed the rights owned by an creator. Protection of a creation is provided by the Berne Convention and also the laws of each participating country. In other words, every country participants are obliged to provide protection to the creation of all citizens countries from all participating countries that are participants in the Berne Convention. Where the protection of the creation will be further regulated by: the law of the country of origin of the creator or the law of the country of place claimed protection. In this article, we will explain more about protection the law against the songwriter Aisyah from Malaysia with reference to Indonesian state laws and regulations, because in this case the perpetrators of copyright infringement are indonesian citizens. The type of research that used is by using normative juridical. Keywords: Legal Protection, Creator, Youtube Content Strike